Acute kidney injury in the UK: a replication cohort study of the variation across three regional populations. Issue 6 (30th June 2018) - Sawhney, Simon; Robinson, Heather A; van der Veer, Sabine N; Hounkpatin, Hilda O; Scale, Timothy M; Chess, James A; Peek, Niels; Marks, Angharad; Davies, Gareth Ivor; Fraccaro, Paolo; Johnson, Matthew J; Lyons, Ronan A; et al.
Abstract : Objectives: A rapid growth in the reported rates of acute kidney injury (AKI) has led to calls for greater attention and greater resources for improving care. However, the reported incidence of AKI also varies more than tenfold between previous studies. Some of this variation is likely to stem from methodological heterogeneity. This study explores the extent of cross-population variation in AKI incidence after minimising heterogeneity. Design: Population-based cohort study analysing data from electronic health records from three regions in the UK through shared analysis code and harmonised methodology. Setting: Three populations from Scotland, Wales and England covering three time periods: Grampian 2003, 2007 and 2012; Swansea 2007; and Salford 2012. Participants: All residents in each region, aged 15 years or older. Main outcome measures: Population incidence of AKI and AKI phenotype (severity, recovery, recurrence). Determined using shared biochemistry-based AKI episode code and standardised by age and sex. Results: Respectively, crude AKI rates (per 10 000/year) were 131, 138, 139, 151 and 124 (p=0.095), and after standardisation for age and sex: 147, 151, 146, 146 and 142 (p=0.257) for Grampian 2003, 2007 and 2012; Swansea 2007; and Salford 2012. The pattern of variation in crude rates was robust to any modifications of the AKI definition. Across all populations and time periods, AKI rates increased substantially with age from ~20 to ~550 per 10 000/year among those aged <40 and ≥70 years. Conclusion: When harmonised methods are used and age and sex differences are accounted for, a similar high burden of AKI is consistently observed across different populations and time periods (~150 per 10 000/year). There are particularly high rates of AKI among older people. Policy-makers should be careful not draw simplistic assumptions about variation in AKI rates based on comparisons that are not rigorous in methodological terms.